2019
DOI: 10.1016/j.celrep.2019.05.104
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cholesterol Biosynthesis Is a Key Characteristic of Breast Cancer Stem Cells Influencing Patient Outcome

Abstract: Highlights d Cholesterol biosynthesis is essential for breast cancer stem cell propagation d Expression of cholesterol synthesis proteins correlates with TNBC patient outcome d Inhibition of cholesterol biosynthesis reduces mammosphere formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 58 publications
(62 reference statements)
4
115
0
Order By: Relevance
“…Also in this case, analysis of affected signaling processes performed on a lists of deregulated miRNA targets revealed mainly histotype-specific changes, with the only common group of signaling pathways consisting of all branches of cholesterol biosynthesis, in line with our previous results concerning ERβ-induced inhibition of cholesterol biosynthesis in TNBC [15]. Moreover, one recently published study demonstrated that cholesterol biosynthesis is essential for breast cancer stem cell propagation [77], whereas another showed that the hyper-activated cholesterol biosynthesis program of TNBC is regulated by nuclear receptor RORγ (RAR-related orphan receptor gamma), whose inhibition by receptor antagonists leads to tumor regression in patient-derived xenografts and immune-intact models [78], confirming the extreme importance of cholesterol biosynthesis in TNBC cancer progression.…”
Section: Discussionsupporting
confidence: 88%
“…Also in this case, analysis of affected signaling processes performed on a lists of deregulated miRNA targets revealed mainly histotype-specific changes, with the only common group of signaling pathways consisting of all branches of cholesterol biosynthesis, in line with our previous results concerning ERβ-induced inhibition of cholesterol biosynthesis in TNBC [15]. Moreover, one recently published study demonstrated that cholesterol biosynthesis is essential for breast cancer stem cell propagation [77], whereas another showed that the hyper-activated cholesterol biosynthesis program of TNBC is regulated by nuclear receptor RORγ (RAR-related orphan receptor gamma), whose inhibition by receptor antagonists leads to tumor regression in patient-derived xenografts and immune-intact models [78], confirming the extreme importance of cholesterol biosynthesis in TNBC cancer progression.…”
Section: Discussionsupporting
confidence: 88%
“…cholesterol and lipid rafts (41,57). In addition, recent data revealed the activation of cholesterol biosynthesis pathways in cancer stem cells (42) Heterogeneity of glioma determined by TOF-SIMS 20 the clinical and histological features of the tumor, and in some cases, it allows to subdivide patients into groups characterized by more favorable and less favorable survival. Since TOF-SIMS does not require specific sample preparation procedures, and the analysis of one sample takes less than 10 minutes, it is possible that after further development this technology can be used for the rapid identification of GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in good agreement with our hypothesis that the cholesterol high /Caveolin-1 high population of GBM cells found using TOF-SIMS may represent GSC. This hypothesis is also indirectly supported by the fact that cancer stem cells are characterized by an increased level of cholesterol biosynthesis (42).…”
Section: Detection Of Caveolin-1 Protein and Cholesterol In Gbm Cellsmentioning
confidence: 94%
“…Cholesterol biosynthesis also has a critical role in maintaining cancer stem cells by activating cellular signalling pathways downstream of sonic hedgehog, Notch and receptor tyrosine kinases 30 . Furthermore, elevated cholesterol biosynthesis is observed in patient-derived cancer stem cells under mammosphere culture conditions 31 . These lines of evidence suggest that ensuring a sufficient cholesterol supply for the cancer stem cell population may be essential to support cancer progression, thus highlighting a fundamental role of cholesterol in cancer cells.…”
mentioning
confidence: 99%